Feasibility, safety, and adherence of home-based exercise interventions in people diagnosed with cancer: a systematic review - Su, Jing Jing; Winnige, Petr; Chamradova, Katerina; Dosbaba, Filip; Batalikova, Katerina; Lin, Rose; Antoniou, Varsamo; Pepera, Garyfallia; Batalik, Ladislav (Journal of cancer survivorship, 2025)
PURPOSE: This systematic review aims to evaluate the feasibility, safety, and adherence of home-based exercise interventions in people diagnosed with cancer. The primary research question is: Are home-based exercise interventions safe and feasible for people diagnosed with cancer? METHODS: A comprehensive search of databases including PubMed, EMBASE, and Cochrane Library was conducted in January 2025, focusing on randomized controlled trials (RCTs) that involved home-based exercise interventions people diagnosed with cancer. Studies were included if they reported on safety, feasibility, and health-related outcomes. The Physiotherapy Evidence Database (PEDro) scale was used to assess study quality and risk of bias. Adverse events were categorized by severity, and feasibility which was determined based on recruitment, withdrawal, and adherence rates. RESULTS: From 127 eligible studies involving 10,562 participants, the review found that home-based exercise interventions are generally safe, with less than 3.2% of participants experiencing exercise-related adverse events, most of which were minor. Feasibility was supported by an average recruitment rate of 50.1%, which was calculated as the proportion of eligible participants who consented to participate across the included studies. Additionally, the review found a withdrawal rate of 13.7%, and an adherence rate of 76.2%. However, significant variability in these rates were observed across the studies, highlighting the challenges in maintaining participant engagement. CONCLUSIONS: Home-based exercise interventions are feasible and safe for people diagnosed with cancer, with minor adverse events being the most common. However, there is a need for standardized protocols in reporting adverse events and better strategies to improve recruitment and adherence. IMPLICATIONS FOR CANCER SURVIVORS: These findings support the integration of home-based exercise into standard cancer care, offering a practical and safe option for enhancing the health and well-being of cancer survivors. However, the successful implementation of these programs may require additional support from exercise professionals within primary care or community settings to ensure appropriate guidance and adherence. Personalized exercise programs, developed by qualified exercise professionals such as physiotherapists or clinical exercise physiologists, and improved reporting standards are essential to optimizing these interventions.
Keywords: Cancer survivors; Safety; Physical activity; Adherence; Adverse events; Feasibility; Home-based exercise